Accompaniment of Initial Teacher Training Practices: Characteristics of the Trainers’ Identity Processes; [Acompañamiento de Prácticas de Formación Inicial del Profesorado: Características de Los Procesos Identitarios de Los Formadores] - Vanegas-Ortega, C (Centro de Informacion Tecnologica, 2023)
The main objective of this study is to characterize the identity processes of teacher educators during the accompaniment of the pedagogical practices of initial teacher training. Initial teacher training practices are accompanied by two trainers: the university tutor and the school guide. However, it is not sufficient to be a teacher to play these roles as an identity as a trainer is required. A qualitative case study is conducted for one year with tutors and guides who accompany different levels of practice through in-depth interviews and focus groups. The results show that tutor teachers recognize differences between their professional teaching identities and their role identities, while guide teachers identify with their roles in diffuse or unclear manners. In conclusion, there is the need to promote in tutors and guides their identity processes, skills, and resources that validate them as trainers. © (2023), (Centro de Informacion Tecnologica). All Rights Reserved.